How remote labs impact on course outcomes: various practices using VISIR - Marques, Maria A. (2014)
As technology is increasingly being seen as a facilitator to learning, open remote laboratories are increasingly available and in widespread use around the world. They provide some advantages over traditional hands-on labs or simulations. This paper presents the results of integrating the open remote laboratory VISIR into several courses, in various contexts and using various methodologies. These integrations, all related to higher education engineering, were designed by teachers with different perspectives to achieve a range of learning outcomes. The degree to which these VISIR-related outcomes were accomplished is discussed. The results reflect the levels of student engagement and learning and of teacher involvement. From the analysis, a connection between these two aspects was traced, although only related to the user profiles. VISIR is shown to be always of benefit for more motivated students, but this benefit can be maximized under particular conditions and characteristics.